Mechanism and Characteristics of CH4/CO2/H2O Adsorption in Lignite Molecules - Zhihui Wen; Yunpeng Yang; Qi Wang; Banghua Yao (Geofluids)
Adsorption characteristics of coalbed methane (CBM) are significant to investigate the absorption of coal, shale, and porous media. In particular, adsorption characteristics of CH4, CO2, and H2O play an important role in predicting CBM output and geologic sequestration potentials of CO2 in research fields of CO2-enhanced CBM recovery (CO2-ECBM) and sequestration of CO2. In this work, adsorption characteristics of CH4, CO2, and H2O in lignite molecules were simulated through the grand canonical Monte Carlo (GCMC) method and molecular dynamics (MD) method. Research results demonstrated that given the same temperature and pressure, the ultimate adsorption capacity of lignite per unit to H2O is the highest, followed by those of CO2 and CH4 successively. All isothermal adsorption curves conform to the “I-type” characteristics. In the saturated molecular configuration, gas molecules show different distribution patterns at two sides of the lignite molecule chain. Lignite has typical physical adsorption to CH4 and CO2, with adsorption energy provided by nonbonding energy. However, lignite has both physical adsorption and chemical adsorption to H2O, with adsorption energy provided by both nonbonding energy and hydrogen bond energy. High temperature is against adsorption of CH4, CO2, and H2O. Temperature might inhibit adsorption of gas molecules. Research conclusions lay foundations for the exploitation and development of CBM and relevant studies on sequestration of CO2.